Identification of Novel Coumestan Derivatives as Polyketide Synthase 13 Inhibitors against Mycobacterium tuberculosis - Zhang, W.; Lun, S.; Wang, S.; Jiang, X.; Yang, F.; Tang, J.; Manson, A.; Earl, A.; Gunosewoyo, Hendra; Bishai, W.; Yu, L. (American Chemical Society, 2018)
© 2018 American Chemical Society. Inhibition of the mycolic acid pathway has proven a viable strategy in antitubercular drug discovery. The AccA3/AccD4/FadD32/Pks13 complex of Mycobacterium tuberculosis constitutes an essential biosynthetic mechanism for mycolic acids. Small molecules targeting the thioesterase domain of Pks13 have been reported, including a benzofuran-based compound whose X-ray cocrystal structure has been very recently solved. Its initial inactivity in a serum inhibition titration (SIT) assay led us to further probe other structurally related benzofurans with the aim to improve their potency and bioavailability. Herein, we report our preliminary structure-activity relationship studies around this scaffold, highlighting a natural product-inspired cyclization strategy to form coumestans that are shown to be active in SIT. Whole genome deep sequencing of the coumestan-resistant mutants confirmed a single nucleotide polymorphism in the pks13 gene responsible for the resistance phenotype, demonstrating the druggability of this target for the development of new antitubercular agents.